Nicaragua: Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The overarching goal of this Country Financial Accountability Assessment (CFAA) i s to assist the Government in achieving effective implementation of its strategy for strengthened growth and poverty reduction through good public financial management. Some of the report's general conclusions are as follows: The laws and regulations governing public financial management are generally sound, but need to be consolidated and modernized. The Government has gradually improved budget classification, realism and participation of executing entities in its preparation. Still, there is budget incrementalism and an effective separation of recurrent and investment budgeting. The Government's integrated financial management system has considerably improved public financial management, establishing the concept of increased efficiency through integration of budgeting, accounting, treasury, public debt and procurement. Operation of the treasury single account system has contributed significantly to effective cash position controls, but absence of detailed cash flow programs and presence of global budget transfers prevents adequate cash management. While the integrated financial management system has allowed for effective central controls on overall spending, the internal control and internal audit capacity in spending entities needs improvement. The underlying financial management systems still do not contribute to increased efficiency of service delivery. Public investment planning capacity has increased, but deficient monitoring and evaluation systems help perpetuate the existence of obsolete and ineffective programs. Although budget execution reports are prepared on time, the lack of adequate government financial statements and institutionalized public sector accounting affects the review and analysis of public finances. The lack of external audit reports on government financial statements is a serious obstacle to transparency in public finances. The institutional foundations to allow for public scrutiny of public expenditure are already in place, but effective implementation requires dealing with significant challenges posed by the lack of traditions of public consultation and of meaningful public access to information, the abstract and complicated nature of available information on public finances, and the physical difficulty of accessing the information. Other conclusions concerned external aid channeling practices, civil service reform, public debt management, and generally weak revenue administration.